Wahdatul Ulum's Paradigm Punch in Islamic Philosophy and Science - Dede Khairani; Salminawati, Salminawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to review the Definition of the Wahdatul ulum Paradigm with a Transdisciplinary Approach. The separation between religious knowledge and general science has long occurred. Some Muslim communities still believe that religion and science cannot be combined together because they both have their own domains. With a transdisciplinary approach, Wahdatul `Ulum is very suitable in the current uncertain era where advances in digital technology are the main factor. Research is qualitative research on library studies (library research), collecting data by looking for sources such as books, journals and previous research. Transdisciplinarity is reflection, integration and methods that go beyond scientific principles with the aim of finding solutions to social problems, which are obtained from combining related sciences in a way that differentiates and integrates knowledge from various theories. A transdisciplinary approach implies full interaction between, between, and outside disciplines from a perspective or based on real-life problems. The results of this research conclude that all UINs in Indonesia must have an attitude of adapting to all kinds of changes, especially North Sumatra UIN. As an Islamic-based university, it follows the concept of the Wahdatul Ulum paradigm through an interdisciplinary approach, referring to the values contained in various articles about the implementation of education, research and public works at the Islamic Religious University of North Sumatra.